2002
DOI: 10.1139/x02-088
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting modes of survival by jack and pitch pine at a common range limit

Abstract: Freezing tolerance, reproductive development, and seed germination of jack pine (Pinus banksiana Lamb.) and pitch pine (Pinus rigida Mill.) were compared in a small sympatric population in Acadia National Park in Maine, at the southern range limit of the former and the northern limit of the latter. Freezing tolerances of vegetative shoots and roots were similar for both species. Both species flower prolifically, and there was no evidence of differences in either pollen viability, cone survival, or proportion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…There are many possible drivers including seed production (Greenwood et al 2002;LaDeau and Clark 2001); seed dispersal (Higgins et al 2003); seedling establishment ); competition for nutrients; water and light (Gleeson and Tilman 1990); forest diebacks (Auclair 1993;Cox et al 2004); herbivores (Howlett and Davidson 2003); pathogens and parasites (Moorcroft et al 2006); and genetic adaptation (Bradshaw and Holzapfel 2006). In our study, response of species' colonization ability to climatic change was governed by the modification of seedling establishment probability.…”
Section: Discussionmentioning
confidence: 71%
“…There are many possible drivers including seed production (Greenwood et al 2002;LaDeau and Clark 2001); seed dispersal (Higgins et al 2003); seedling establishment ); competition for nutrients; water and light (Gleeson and Tilman 1990); forest diebacks (Auclair 1993;Cox et al 2004); herbivores (Howlett and Davidson 2003); pathogens and parasites (Moorcroft et al 2006); and genetic adaptation (Bradshaw and Holzapfel 2006). In our study, response of species' colonization ability to climatic change was governed by the modification of seedling establishment probability.…”
Section: Discussionmentioning
confidence: 71%
“…In these populations, Conkey et al (1995) found that mature trees of both species showed good growth and no signs of speciesspecific stress. We have shown that neither freezetolerance nor reproductive efforts are limiting for either species where their populations overlap at ANP (Greenwood et al, 2002). However, the two species differ in their seed germination trajectories with respect to temperature, with jack pine germinating faster at relatively lower temperatures.…”
Section: Introductionmentioning
confidence: 87%
“…However, the two species differ in their seed germination trajectories with respect to temperature, with jack pine germinating faster at relatively lower temperatures. This may provide an early growth advantage to jack pine when soil temperatures are low (Greenwood et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pitch pine was selected as the prime recorder of forest history, given its site age and the fact that much of dendroecological record in this region has either been logged or consumed by fire. Additionally, pitch pine is generally shade-intolerant and establishment is best on bare mineral soil (Greenwood et al 2002), such that its presence within the contemporary mesophytic forest is an indicator, or legacy, of past disturbance. Specifically, my objectives were to (1) develop the first large sample tree-ring record that pre-dates industrialization in the New River Gorge region; (2) reconstruct the fire and canopy disturbance history of a mixed pine-oak community embedded within the mesophytic forest region; and (3) test the relationship between climate and disturbance in the context of land use change and industrialization.…”
Section: Introductionmentioning
confidence: 99%